MCEEC: Multi-hop Centralized Energy Efficient Clustering routing protocol for WSNs - Javaid, N.; Aslam, M.; Ahmad, A.; Khan, Z. A.; Alghamdi, T. A. (2014 IEEE International Conference on Communications (ICC), 2014)
In order to increase the network lifetime, scalable and energy-aware routing protocols are very essential for Wireless Sensor Networks (WSNs). In this paper, we propose a heterogeneity-aware Multi-hop Centralized Energy Efficient Clustering (MCEEC) protocol for routing in WSNs. Operation of MCEEC is based upon the advanced central control algorithm, in which Base Station (BS) is responsible for the selection of Cluster-Heads (CHs) which are selected on the bases of wireless sensors' (nodes') residual energy, average energy of the network, and average of the relative distance between nodes and BS. We adopt multi-hop inter-cluster communication for MCEEC. The advanced heterogeneous network model of the proposed protocol divides the network area into three equally spaced rectangular regions such that nodes of the same energy level are deployed in the respective region. Furthermore, nodes can only associate with their own region's CHs. In MCEEC, deployment of nodes in the network area is in descending order of energy level w.r.t BS's position. Simulation results show that MCEEC yields maximum scalability, network lifetime, stability period and throughput as compared to the selected routing protocols.